PRODUCT DAN PROMOTION TERHADAP CUSTOMER SATISFACTION FIKA KEDAI KAFI KARAWACI - JULIANA .; CAROLINE WIDJAJA; EUGENE MARSANO; KEVIN WIJAYA; SELLY . (LP2MTBM MAKARIOZ, 2020)
The research objective was to analyze the effect of product and promotion on customer satisfaction at Fika Kedai KafiKarawaci. And this study also aims to analyze the factors that have the most dominant influence on customer satisfaction atFika Kedai Kafi Karawaci. The population used in this study are customers or consumers who have tried Fika Kedai KafiKarawaci products. The number of samples in this study were 60 respondents. Data collection was carried out by using aquestionnaire method. The data obtained were analyzed by using the Validity Test, Reliability Test, Linear Analysis ofMultiple Regression, Analysis of the Coefficient of Determination (R2), and Hypothesis Test with the F test and t test. Fromthe analysis, the indicators in this study are valid and reliable. The variable with the most dominant influence on customersatisfaction is the product variable with a regression coefficient of 0.878. Meanwhile, the promotion variable has a regressioncoefficient of 0.093. The results showed that the product and promotion simultaneously affect customer satisfaction at FikaKedai Kafi Karawaci. Products have a positive and significant effect on customer satisfaction at Fika Kedai Kafi Karawaci.Meanwhile, promotion does not significantly influence customer satisfaction at Fika Kedai Kafi Karawaci.